Analisis Faktor-Faktor Yang Mempengaruhi Produksi Singkong (Manihot Esculenta) Di Desa Buaran Kecamatan Mayong Kabupaten Jepara - Novi Fitri Ariyani; Istanto .; Sri Wahyuningsih; Rossi Prabowo (Jurnal Ekonomi Pertanian dan Agribisnis, 2026)
Production is the result of a combination of various production factors. Therefore, to achieve optimal production, it is necessary to combine production factors appropriately. This study aims to analyze the influence of land area, seeds, fertilizers, pesticides, and labor on cassava production, both simultaneously and partially, in Buaran Village. This study is a quantitative study. The study was conducted in Buaran Village, Mayong District, Jepara Regency because Buaran Village is the area within Mayong District with the largest cassava land and production. The population in this study was all farmers who grow cassava in rice fields, gardens, farms, and dry fields. A sample of 50 respondents was selected using a simple random sampling technique. Data collection used a questionnaire, and data analysis used the Cobb-Douglas analysis and the classical assumption test. The results showed that land area, seeds, fertilizer, pesticides, and labor simultaneously influenced cassava production. At the 5% significance level, land area, seeds, fertilizer, and labor significantly influenced cassava production, while pesticides did not have a partial significant effect on cassava production because the probability value was greater than the 5% significance level.